Core arbuscular mycorrhizal fungi are predicted by their high abundance–occupancy relationship while host‐specific taxa are rare and geographically structured. Issue 4 (21st March 2022) - Kajihara, Kacie T.; Egan, Cameron P.; Swift, Sean O. I.; Wall, Christopher B.; Muir, Christopher D.; Hynson, Nicole A.
Summary: Habitat restoration may depend on the recovery of plant microbial symbionts such as arbuscular mycorrhizal (AM) fungi, but this requires a better understanding of the rules that govern their community assembly. We examined the interactions of soil and host‐associated AM fungal communities between remnant and restored patches of subtropical montane forests. While AM fungal richness did not differ between habitat types, community membership did and was influenced by geography, habitat and host. These differences were largely driven by rare host‐specific AM fungi that displayed near‐complete turnover between forest types, while core AM fungal taxa were highly abundant and ubiquitous. The bipartite networks in the remnant forest were more specialized and hosts more specific than in the restored forest. Host‐associated AM fungal communities nested within soil communities in both habitats, but only significantly so in the restored forest. Our results provide evidence that restored and remnant forests harbour the same core fungal symbionts, while rare host‐specific taxa differ, and that geography, host identity and taxonomic resolution strongly affect the observed distribution patterns of these fungi. We suggest that host‐specific interactions with AM fungi, as well as spatial processes, should be explicitly considered to effectively re‐establish target host and symbiont communities.